English Skills for Non-English Major Students: A Need Analysis Survey at a University in Jambi - Failasofah, Failasofah; Safitri, Nyimas Triyana; Anastasia, Indri; Armiwati, Armiwati; Safitri, Angelina Bella (Universitas Batanghari Jambi, 2025)
This study aims to identify and find out the English needs of Non-English Major (NEM) students at the Faculty of Teacher Training and Education (FKIP), Jambi University. Needs analysis in English learning focuses on targets (target needs) and learning needs (learning needs). This is intended to achieve more effective and comprehensive English learning that is truly in accordance with the needs and fields of science of the students. It is also expected that English learning can facilitate students to easily communicate with the fields of science they are studying and master English for learners with specific goals. This study involved around 400 students in the odd academic year 2024/2025 FKIP, Jambi University. The exploratory survey technique used for data collection was to conduct a questionnaire. The technique of analyzing data using Analysis Descriptive Statistics. The results of the study are expected to be the right reference and reference for designing and developing learning tools, especially in the English Course for NEM Students at FKIP, Jambi University.